Optimized absorption imaging of mesoscopic atomic clouds - Müssel, Wolfgang; Strobel, Helmut; Joos, Maxime; Nicklas, Eike; Stroescu, Ion; Tomkovič, Jiří; Hume, David B.; Oberthaler, Markus K. (Applied physics. B, Lasers and optics, 2013)
We report on the optimization of high-intensity absorption imaging for small Bose-Einstein condensates. The imaging calibration exploits the linear scaling of the quantum projection noise with the mean number of atoms for a coherent spin state. After optimization for atomic clouds containing up to 300 atoms, we find an atom number resolution of $$\varDelta_{\rm det}= 3.7$$atoms, mainly limited by photon shot noise and radiation pressure.
Gesehen am 29.06.2021